Diabetes mellitus and venous thromboembolism: A systematic review and meta-analysis. - Bell, Elizabeth J; Folsom, Aaron R; Lutsey, Pamela L; Selvin, Elizabeth; Zakai, Neil A; Cushman, Mary; Alonso, Alvaro (Diabetes Res Clin Pract, 2016)
UNLABELLED: Diabetes mellitus (DM) may be a risk factor for venous thromboembolism (VTE) but results are inconsistent. AIM: We conducted a systematic review and meta-analysis of epidemiologic studies to quantify the association between DM and VTE. METHODS AND RESULTS: We included studies identified in PubMed, Web of Science, and CINAHL through 07/31/2014. We identified 19 studies that met our selection criteria. We pooled RRs using a random-effects model: the pooled RR for the association of DM with VTE was 1.10 (95% CI: 0.94-1.29). Between-study heterogeneity was explored with a forest plot, funnel plot, meta-regression, and a stratified analysis. Between-study heterogeneity was observed and not explained by study design, method of DM assessment, or degree of adjustment for confounding. Sensitivity analyses omitted one study at a time to assess the influence of any single study on the pooled estimate. These analyses indicated that one large study was highly influential; when this study was excluded, the pooled estimate increased and just reached statistical significance: 1.16 (95% CI: 1.01-1.34). CONCLUSIONS: This meta-analysis suggests either no association or a modest positive one between DM and VTE in the general population. DM is unlikely to play a major role in VTE development.